(untitled) (Лучшие интеллектуальные исследования, 2025)
ABSTRACT: Artificial Intelligence (AI) is rapidly reshaping modern industries and economies by transforming how work is performed, decisions are made, and services are delivered. As AI technologies become increasingly integrated into business operations and public systems, they are redefining employment policies, influencing regional development, and demanding new forms of human capital. The evolution of the labor market under AI pressure calls for a reevaluation of workforce skills and targeted investment in education and training. While AI drives economic growth through innovation and productivity, it can also exacerbate regional disparities if strategic employment strategies are not implemented. This paper examines the intersection of AI with labor economics, highlighting the importance of adaptive policies that ensure inclusive development and sustainable workforce transformation.